Coral recruitment before and after bleaching event 2010 in Pulau Weh, Aceh, Indonesia - Zulfikar, Zulfikar; Yasin, Zulfikar; Hwai, Aileen Tan Shaw; Ern, Ng Jol (Universitas Malikussaleh, 2015)
A monitoring study was conducted at Pulau Weh, which is located in Sabang Province Aceh, Indonesia in the northern part of Sumatera from April 2010 to April 2013. This study aims to monitor and evaluate the current status of coral reef, compotition and abundance of juvenile corals on natural substrates and recruits in the chosen sampling sites. Six sampling stations were chosen to determine the changes in coral reef after bleaching event and two stations were chosen to study coral recruitment. The survey was conducted using 5x5m permanent quadrate, placed at two different depths: 4m and 8m. Photo Quadrate method was applied to monitor the coral changes and the recovery of coral reefs in Pulau weh. Where at each sampling location within the quadrate, a series of photographs was taken with a digital camera with wide angle lens and analyzed in the laboratory. A digital probe was placed at each site, where by the temperature was recorded every 2 hours starting from April 2010 to September 2011. An increasing and extreme temperature shock was recorded in May 2010, where the highest temperature recorded was as high as 32 °C for a long duration. From the series of observation, 85% of the coral coverage in the study area in the six sampling site was found bleached and dead during the bleaching phenomena in May to July 2010. The overall number and density of juvenile corals were higher in the upper reef than the lower reef. Low coral recruitment occurred during the sampling periods interfered with disturbances (bleaching event and storm) compared to normal sampling period without disturbance.Penelitian ini dilakukan di Pulau Weh, yang terletak di Provinsi Aceh, Indonesia mulai dari bulan April 2010 sampai dengan April 2013. Penelitian ini bertujuan untuk memantau dan mengevaluasi status terumbu karang, komposisi dan kelimpahan juvenil karang pada substrat alami dan rekrutmen di lokasi yang sudah ditentukan. Enam stasiun pengambilan dipilih untuk melihat perubahan terumbu karang setelah peristiwa pemutihan berlangsung dan dua stasiun dipilih untuk melihat rekrutmen karang baru. Survei ini dilakukan dengan menggunakan kuadrat permanen yang berukuran 5x5m yang ditempatkan pada dua kedalaman yang berbeda yaitu: 4m dan 8m. MetodeFoto Kuadrat diaplikasikan untuk memantau perubahan karang dan pemulihan terumbu karang di Pulau weh setelah peristiwa pemutihan. Foto hasil pengambilan gambar dengan kamera bawah air selanjutnya dianalisis di laboratorium. Alat perekam suhu dan cahaya digital ditempatkan di setiap lokasi penelitian, dimana suhu akan direkam setiap 2 jam sekali mulai dari April 2010 sampai September 2011. Peningkatan suhu secara ekstrim telah dicatat pada bulan Mei 2010 yaitu setinggi 32 °C dalam jangka waktu yang lama. Dari serangkaian pengamatan 85% dari tutupan karang di daerah penelitian ditemukan mati disebabkan fenomena bleaching bulan Mei-Juli 2010. Jumlah keseluruhan dan kepadatan juvenile karang lebih tinggi pada terumbu bagian atas daripada karang yang lebih rendah. Rekrutmen karang yang rendah terjadi selama periode bleaching berlangsung dibandingkan dengan periode sampling normal tanpa gangguan.